Isoelectric points and surface hydrophobicity of Gram-positive cocci as determined by cross-partition and hydrophobic affinity partition in aqueous two-phase systems. - Miörner, H (1982)
Thirty-nine streptococcal strains belonging to groups A, C, and G and 12 staphylococcal strains were investigated with respect to surface charge and hydrophobicity. Isoelectric points of the bacteria were determined by cross-partition experiments in dextran-polyethylene glycol two-phase systems containing charged polymers. The results obtained indicate that group A, C, and G streptococci have isoelectric points of pH 3.75 +/- 0.15 standard deviation. Staphylococci show an isoelectric point of around pH 2 and thereby differ markedly from the streptococci. Pretreatment of bacteria with human serum resulted in a significant change in the isoelectric points of streptococci. In a second series of experiments, an aqueous dextran-polyethylene glycol two-phase system containing polyethylene glycol palmitate or stearate was used to study the hydrophobic surface properties of the bacterial cells. The partition of the staphylococci was not influenced by the addition of up to 1% (wt/wt) polyethylene glycol palmitate or stearate, whereas the streptococci showed a large variation in affinity for polyethylene glycol-bound hydrophobic groups. The bacterial strains included in the study were also tested for uptake of human serum proteins. A positive correlation was found between the hydrophobic affinity of group A streptococci and the density of receptors for aggregated beta-2-microglobulin.